Calculus Examples
f(x)=x4-3x2
Step 1
Step 1.1
Find the first derivative.
Step 1.1.1
Differentiate.
Step 1.1.1.1
By the Sum Rule, the derivative of x4-3x2 with respect to x is ddx[x4]+ddx[-3x2].
f′(x)=ddx(x4)+ddx(-3x2)
Step 1.1.1.2
Differentiate using the Power Rule which states that ddx[xn] is nxn-1 where n=4.
f′(x)=4x3+ddx(-3x2)
f′(x)=4x3+ddx(-3x2)
Step 1.1.2
Evaluate ddx[-3x2].
Step 1.1.2.1
Since -3 is constant with respect to x, the derivative of -3x2 with respect to x is -3ddx[x2].
f′(x)=4x3-3ddxx2
Step 1.1.2.2
Differentiate using the Power Rule which states that ddx[xn] is nxn-1 where n=2.
f′(x)=4x3-3(2x)
Step 1.1.2.3
Multiply 2 by -3.
f′(x)=4x3-6x
f′(x)=4x3-6x
f′(x)=4x3-6x
Step 1.2
Find the second derivative.
Step 1.2.1
By the Sum Rule, the derivative of 4x3-6x with respect to x is ddx[4x3]+ddx[-6x].
f′′(x)=ddx(4x3)+ddx(-6x)
Step 1.2.2
Evaluate ddx[4x3].
Step 1.2.2.1
Since 4 is constant with respect to x, the derivative of 4x3 with respect to x is 4ddx[x3].
f′′(x)=4ddx(x3)+ddx(-6x)
Step 1.2.2.2
Differentiate using the Power Rule which states that ddx[xn] is nxn-1 where n=3.
f′′(x)=4(3x2)+ddx(-6x)
Step 1.2.2.3
Multiply 3 by 4.
f′′(x)=12x2+ddx(-6x)
f′′(x)=12x2+ddx(-6x)
Step 1.2.3
Evaluate ddx[-6x].
Step 1.2.3.1
Since -6 is constant with respect to x, the derivative of -6x with respect to x is -6ddx[x].
f′′(x)=12x2-6ddxx
Step 1.2.3.2
Differentiate using the Power Rule which states that ddx[xn] is nxn-1 where n=1.
f′′(x)=12x2-6⋅1
Step 1.2.3.3
Multiply -6 by 1.
f′′(x)=12x2-6
f′′(x)=12x2-6
f′′(x)=12x2-6
Step 1.3
The second derivative of f(x) with respect to x is 12x2-6.
12x2-6
12x2-6
Step 2
Step 2.1
Set the second derivative equal to 0.
12x2-6=0
Step 2.2
Add 6 to both sides of the equation.
12x2=6
Step 2.3
Divide each term in 12x2=6 by 12 and simplify.
Step 2.3.1
Divide each term in 12x2=6 by 12.
12x212=612
Step 2.3.2
Simplify the left side.
Step 2.3.2.1
Cancel the common factor of 12.
Step 2.3.2.1.1
Cancel the common factor.
12x212=612
Step 2.3.2.1.2
Divide x2 by 1.
x2=612
x2=612
x2=612
Step 2.3.3
Simplify the right side.
Step 2.3.3.1
Cancel the common factor of 6 and 12.
Step 2.3.3.1.1
Factor 6 out of 6.
x2=6(1)12
Step 2.3.3.1.2
Cancel the common factors.
Step 2.3.3.1.2.1
Factor 6 out of 12.
x2=6⋅16⋅2
Step 2.3.3.1.2.2
Cancel the common factor.
x2=6⋅16⋅2
Step 2.3.3.1.2.3
Rewrite the expression.
x2=12
x2=12
x2=12
x2=12
x2=12
Step 2.4
Take the specified root of both sides of the equation to eliminate the exponent on the left side.
x=±√12
Step 2.5
Simplify ±√12.
Step 2.5.1
Rewrite √12 as √1√2.
x=±√1√2
Step 2.5.2
Any root of 1 is 1.
x=±1√2
Step 2.5.3
Multiply 1√2 by √2√2.
x=±1√2⋅√2√2
Step 2.5.4
Combine and simplify the denominator.
Step 2.5.4.1
Multiply 1√2 by √2√2.
x=±√2√2√2
Step 2.5.4.2
Raise √2 to the power of 1.
x=±√2√21√2
Step 2.5.4.3
Raise √2 to the power of 1.
x=±√2√21√21
Step 2.5.4.4
Use the power rule aman=am+n to combine exponents.
x=±√2√21+1
Step 2.5.4.5
Add 1 and 1.
x=±√2√22
Step 2.5.4.6
Rewrite √22 as 2.
Step 2.5.4.6.1
Use n√ax=axn to rewrite √2 as 212.
x=±√2(212)2
Step 2.5.4.6.2
Apply the power rule and multiply exponents, (am)n=amn.
x=±√2212⋅2
Step 2.5.4.6.3
Combine 12 and 2.
x=±√2222
Step 2.5.4.6.4
Cancel the common factor of 2.
Step 2.5.4.6.4.1
Cancel the common factor.
x=±√2222
Step 2.5.4.6.4.2
Rewrite the expression.
x=±√221
x=±√221
Step 2.5.4.6.5
Evaluate the exponent.
x=±√22
x=±√22
x=±√22
x=±√22
Step 2.6
The complete solution is the result of both the positive and negative portions of the solution.
Step 2.6.1
First, use the positive value of the ± to find the first solution.
x=√22
Step 2.6.2
Next, use the negative value of the ± to find the second solution.
x=-√22
Step 2.6.3
The complete solution is the result of both the positive and negative portions of the solution.
x=√22,-√22
x=√22,-√22
x=√22,-√22
Step 3
Step 3.1
Substitute √22 in f(x)=x4-3x2 to find the value of y.
Step 3.1.1
Replace the variable x with √22 in the expression.
f(√22)=(√22)4-3(√22)2
Step 3.1.2
Simplify the result.
Step 3.1.2.1
Simplify each term.
Step 3.1.2.1.1
Apply the product rule to √22.
f(√22)=√2424-3(√22)2
Step 3.1.2.1.2
Simplify the numerator.
Step 3.1.2.1.2.1
Rewrite √24 as 22.
Step 3.1.2.1.2.1.1
Use n√ax=axn to rewrite √2 as 212.
f(√22)=(212)424-3(√22)2
Step 3.1.2.1.2.1.2
Apply the power rule and multiply exponents, (am)n=amn.
f(√22)=212⋅424-3(√22)2
Step 3.1.2.1.2.1.3
Combine 12 and 4.
f(√22)=24224-3(√22)2
Step 3.1.2.1.2.1.4
Cancel the common factor of 4 and 2.
Step 3.1.2.1.2.1.4.1
Factor 2 out of 4.
f(√22)=22⋅2224-3(√22)2
Step 3.1.2.1.2.1.4.2
Cancel the common factors.
Step 3.1.2.1.2.1.4.2.1
Factor 2 out of 2.
f(√22)=22⋅22(1)24-3(√22)2
Step 3.1.2.1.2.1.4.2.2
Cancel the common factor.
f(√22)=22⋅22⋅124-3(√22)2
Step 3.1.2.1.2.1.4.2.3
Rewrite the expression.
f(√22)=22124-3(√22)2
Step 3.1.2.1.2.1.4.2.4
Divide 2 by 1.
f(√22)=2224-3(√22)2
f(√22)=2224-3(√22)2
f(√22)=2224-3(√22)2
f(√22)=2224-3(√22)2
Step 3.1.2.1.2.2
Raise 2 to the power of 2.
f(√22)=424-3(√22)2
f(√22)=424-3(√22)2
Step 3.1.2.1.3
Raise 2 to the power of 4.
f(√22)=416-3(√22)2
Step 3.1.2.1.4
Cancel the common factor of 4 and 16.
Step 3.1.2.1.4.1
Factor 4 out of 4.
f(√22)=4(1)16-3(√22)2
Step 3.1.2.1.4.2
Cancel the common factors.
Step 3.1.2.1.4.2.1
Factor 4 out of 16.
f(√22)=4⋅14⋅4-3(√22)2
Step 3.1.2.1.4.2.2
Cancel the common factor.
f(√22)=4⋅14⋅4-3(√22)2
Step 3.1.2.1.4.2.3
Rewrite the expression.
f(√22)=14-3(√22)2
f(√22)=14-3(√22)2
f(√22)=14-3(√22)2
Step 3.1.2.1.5
Apply the product rule to √22.
f(√22)=14-3√2222
Step 3.1.2.1.6
Rewrite √22 as 2.
Step 3.1.2.1.6.1
Use n√ax=axn to rewrite √2 as 212.
f(√22)=14-3(212)222
Step 3.1.2.1.6.2
Apply the power rule and multiply exponents, (am)n=amn.
f(√22)=14-3212⋅222
Step 3.1.2.1.6.3
Combine 12 and 2.
f(√22)=14-322222
Step 3.1.2.1.6.4
Cancel the common factor of 2.
Step 3.1.2.1.6.4.1
Cancel the common factor.
f(√22)=14-322222
Step 3.1.2.1.6.4.2
Rewrite the expression.
f(√22)=14-3222
f(√22)=14-3222
Step 3.1.2.1.6.5
Evaluate the exponent.
f(√22)=14-3222
f(√22)=14-3222
Step 3.1.2.1.7
Raise 2 to the power of 2.
f(√22)=14-3(24)
Step 3.1.2.1.8
Cancel the common factor of 2 and 4.
Step 3.1.2.1.8.1
Factor 2 out of 2.
f(√22)=14-32(1)4
Step 3.1.2.1.8.2
Cancel the common factors.
Step 3.1.2.1.8.2.1
Factor 2 out of 4.
f(√22)=14-32⋅12⋅2
Step 3.1.2.1.8.2.2
Cancel the common factor.
f(√22)=14-32⋅12⋅2
Step 3.1.2.1.8.2.3
Rewrite the expression.
f(√22)=14-3(12)
f(√22)=14-3(12)
f(√22)=14-3(12)
Step 3.1.2.1.9
Combine -3 and 12.
f(√22)=14+-32
Step 3.1.2.1.10
Move the negative in front of the fraction.
f(√22)=14-32
f(√22)=14-32
Step 3.1.2.2
To write -32 as a fraction with a common denominator, multiply by 22.
f(√22)=14-32⋅22
Step 3.1.2.3
Write each expression with a common denominator of 4, by multiplying each by an appropriate factor of 1.
Step 3.1.2.3.1
Multiply 32 by 22.
f(√22)=14-3⋅22⋅2
Step 3.1.2.3.2
Multiply 2 by 2.
f(√22)=14-3⋅24
f(√22)=14-3⋅24
Step 3.1.2.4
Combine the numerators over the common denominator.
f(√22)=1-3⋅24
Step 3.1.2.5
Simplify the numerator.
Step 3.1.2.5.1
Multiply -3 by 2.
f(√22)=1-64
Step 3.1.2.5.2
Subtract 6 from 1.
f(√22)=-54
f(√22)=-54
Step 3.1.2.6
Move the negative in front of the fraction.
f(√22)=-54
Step 3.1.2.7
The final answer is -54.
-54
-54
-54
Step 3.2
The point found by substituting √22 in f(x)=x4-3x2 is (√22,-54). This point can be an inflection point.
(√22,-54)
Step 3.3
Substitute -√22 in f(x)=x4-3x2 to find the value of y.
Step 3.3.1
Replace the variable x with -√22 in the expression.
f(-√22)=(-√22)4-3(-√22)2
Step 3.3.2
Simplify the result.
Step 3.3.2.1
Simplify each term.
Step 3.3.2.1.1
Use the power rule (ab)n=anbn to distribute the exponent.
Step 3.3.2.1.1.1
Apply the product rule to -√22.
f(-√22)=(-1)4(√22)4-3(-√22)2
Step 3.3.2.1.1.2
Apply the product rule to √22.
f(-√22)=(-1)4(√2424)-3(-√22)2
f(-√22)=(-1)4(√2424)-3(-√22)2
Step 3.3.2.1.2
Raise -1 to the power of 4.
f(-√22)=1(√2424)-3(-√22)2
Step 3.3.2.1.3
Multiply √2424 by 1.
f(-√22)=√2424-3(-√22)2
Step 3.3.2.1.4
Simplify the numerator.
Step 3.3.2.1.4.1
Rewrite √24 as 22.
Step 3.3.2.1.4.1.1
Use n√ax=axn to rewrite √2 as 212.
f(-√22)=(212)424-3(-√22)2
Step 3.3.2.1.4.1.2
Apply the power rule and multiply exponents, (am)n=amn.
f(-√22)=212⋅424-3(-√22)2
Step 3.3.2.1.4.1.3
Combine 12 and 4.
f(-√22)=24224-3(-√22)2
Step 3.3.2.1.4.1.4
Cancel the common factor of 4 and 2.
Step 3.3.2.1.4.1.4.1
Factor 2 out of 4.
f(-√22)=22⋅2224-3(-√22)2
Step 3.3.2.1.4.1.4.2
Cancel the common factors.
Step 3.3.2.1.4.1.4.2.1
Factor 2 out of 2.
f(-√22)=22⋅22(1)24-3(-√22)2
Step 3.3.2.1.4.1.4.2.2
Cancel the common factor.
f(-√22)=22⋅22⋅124-3(-√22)2
Step 3.3.2.1.4.1.4.2.3
Rewrite the expression.
f(-√22)=22124-3(-√22)2
Step 3.3.2.1.4.1.4.2.4
Divide 2 by 1.
f(-√22)=2224-3(-√22)2
f(-√22)=2224-3(-√22)2
f(-√22)=2224-3(-√22)2
f(-√22)=2224-3(-√22)2
Step 3.3.2.1.4.2
Raise 2 to the power of 2.
f(-√22)=424-3(-√22)2
f(-√22)=424-3(-√22)2
Step 3.3.2.1.5
Raise 2 to the power of 4.
f(-√22)=416-3(-√22)2
Step 3.3.2.1.6
Cancel the common factor of 4 and 16.
Step 3.3.2.1.6.1
Factor 4 out of 4.
f(-√22)=4(1)16-3(-√22)2
Step 3.3.2.1.6.2
Cancel the common factors.
Step 3.3.2.1.6.2.1
Factor 4 out of 16.
f(-√22)=4⋅14⋅4-3(-√22)2
Step 3.3.2.1.6.2.2
Cancel the common factor.
f(-√22)=4⋅14⋅4-3(-√22)2
Step 3.3.2.1.6.2.3
Rewrite the expression.
f(-√22)=14-3(-√22)2
f(-√22)=14-3(-√22)2
f(-√22)=14-3(-√22)2
Step 3.3.2.1.7
Use the power rule (ab)n=anbn to distribute the exponent.
Step 3.3.2.1.7.1
Apply the product rule to -√22.
f(-√22)=14-3((-1)2(√22)2)
Step 3.3.2.1.7.2
Apply the product rule to √22.
f(-√22)=14-3((-1)2(√2222))
f(-√22)=14-3((-1)2(√2222))
Step 3.3.2.1.8
Raise -1 to the power of 2.
f(-√22)=14-3(1(√2222))
Step 3.3.2.1.9
Multiply √2222 by 1.
f(-√22)=14-3√2222
Step 3.3.2.1.10
Rewrite √22 as 2.
Step 3.3.2.1.10.1
Use n√ax=axn to rewrite √2 as 212.
f(-√22)=14-3(212)222
Step 3.3.2.1.10.2
Apply the power rule and multiply exponents, (am)n=amn.
f(-√22)=14-3212⋅222
Step 3.3.2.1.10.3
Combine 12 and 2.
f(-√22)=14-322222
Step 3.3.2.1.10.4
Cancel the common factor of 2.
Step 3.3.2.1.10.4.1
Cancel the common factor.
f(-√22)=14-322222
Step 3.3.2.1.10.4.2
Rewrite the expression.
f(-√22)=14-3222
f(-√22)=14-3222
Step 3.3.2.1.10.5
Evaluate the exponent.
f(-√22)=14-3222
f(-√22)=14-3222
Step 3.3.2.1.11
Raise 2 to the power of 2.
f(-√22)=14-3(24)
Step 3.3.2.1.12
Cancel the common factor of 2 and 4.
Step 3.3.2.1.12.1
Factor 2 out of 2.
f(-√22)=14-32(1)4
Step 3.3.2.1.12.2
Cancel the common factors.
Step 3.3.2.1.12.2.1
Factor 2 out of 4.
f(-√22)=14-32⋅12⋅2
Step 3.3.2.1.12.2.2
Cancel the common factor.
f(-√22)=14-32⋅12⋅2
Step 3.3.2.1.12.2.3
Rewrite the expression.
f(-√22)=14-3(12)
f(-√22)=14-3(12)
f(-√22)=14-3(12)
Step 3.3.2.1.13
Combine -3 and 12.
f(-√22)=14+-32
Step 3.3.2.1.14
Move the negative in front of the fraction.
f(-√22)=14-32
f(-√22)=14-32
Step 3.3.2.2
To write -32 as a fraction with a common denominator, multiply by 22.
f(-√22)=14-32⋅22
Step 3.3.2.3
Write each expression with a common denominator of 4, by multiplying each by an appropriate factor of 1.
Step 3.3.2.3.1
Multiply 32 by 22.
f(-√22)=14-3⋅22⋅2
Step 3.3.2.3.2
Multiply 2 by 2.
f(-√22)=14-3⋅24
f(-√22)=14-3⋅24
Step 3.3.2.4
Combine the numerators over the common denominator.
f(-√22)=1-3⋅24
Step 3.3.2.5
Simplify the numerator.
Step 3.3.2.5.1
Multiply -3 by 2.
f(-√22)=1-64
Step 3.3.2.5.2
Subtract 6 from 1.
f(-√22)=-54
f(-√22)=-54
Step 3.3.2.6
Move the negative in front of the fraction.
f(-√22)=-54
Step 3.3.2.7
The final answer is -54.
-54
-54
-54
Step 3.4
The point found by substituting -√22 in f(x)=x4-3x2 is (-√22,-54). This point can be an inflection point.
(-√22,-54)
Step 3.5
Determine the points that could be inflection points.
(√22,-54),(-√22,-54)
(√22,-54),(-√22,-54)
Step 4
Split (-∞,∞) into intervals around the points that could potentially be inflection points.
(-∞,-√22)∪(-√22,√22)∪(√22,∞)
Step 5
Step 5.1
Replace the variable x with -0.80710678 in the expression.
f′′(-0.80710678)=12(-0.80710678)2-6
Step 5.2
Simplify the result.
Step 5.2.1
Simplify each term.
Step 5.2.1.1
Raise -0.80710678 to the power of 2.
f′′(-0.80710678)=12⋅0.65142135-6
Step 5.2.1.2
Multiply 12 by 0.65142135.
f′′(-0.80710678)=7.81705627-6
f′′(-0.80710678)=7.81705627-6
Step 5.2.2
Subtract 6 from 7.81705627.
f′′(-0.80710678)=1.81705627
Step 5.2.3
The final answer is 1.81705627.
1.81705627
1.81705627
Step 5.3
At -0.80710678, the second derivative is 1.81705627. Since this is positive, the second derivative is increasing on the interval (-∞,-√22).
Increasing on (-∞,-√22) since f′′(x)>0
Increasing on (-∞,-√22) since f′′(x)>0
Step 6
Step 6.1
Replace the variable x with 0 in the expression.
f′′(0)=12(0)2-6
Step 6.2
Simplify the result.
Step 6.2.1
Simplify each term.
Step 6.2.1.1
Raising 0 to any positive power yields 0.
f′′(0)=12⋅0-6
Step 6.2.1.2
Multiply 12 by 0.
f′′(0)=0-6
f′′(0)=0-6
Step 6.2.2
Subtract 6 from 0.
f′′(0)=-6
Step 6.2.3
The final answer is -6.
-6
-6
Step 6.3
At 0, the second derivative is -6. Since this is negative, the second derivative is decreasing on the interval (-√22,√22)
Decreasing on (-√22,√22) since f′′(x)<0
Decreasing on (-√22,√22) since f′′(x)<0
Step 7
Step 7.1
Replace the variable x with 0.80710678 in the expression.
f′′(0.80710678)=12(0.80710678)2-6
Step 7.2
Simplify the result.
Step 7.2.1
Simplify each term.
Step 7.2.1.1
Raise 0.80710678 to the power of 2.
f′′(0.80710678)=12⋅0.65142135-6
Step 7.2.1.2
Multiply 12 by 0.65142135.
f′′(0.80710678)=7.81705627-6
f′′(0.80710678)=7.81705627-6
Step 7.2.2
Subtract 6 from 7.81705627.
f′′(0.80710678)=1.81705627
Step 7.2.3
The final answer is 1.81705627.
1.81705627
1.81705627
Step 7.3
At 0.80710678, the second derivative is 1.81705627. Since this is positive, the second derivative is increasing on the interval (√22,∞).
Increasing on (√22,∞) since f′′(x)>0
Increasing on (√22,∞) since f′′(x)>0
Step 8
An inflection point is a point on a curve at which the concavity changes sign from plus to minus or from minus to plus. The inflection points in this case are (-√22,-54),(√22,-54).
(-√22,-54),(√22,-54)
Step 9